The reliability of a linear position transducer and commercially available accelerometer to measure punching velocity in junior boxing athletes - Harris, D. M.; Caillaud, K.; Khullar, S.; Haff, G. G.; Latella, C. (International Journal of Sports Science & Coaching, 2021)
Limited evidence exists demonstrating reliability of using direct measures to quantify punching velocity. The aim of this study was to establish the intra- and inter-day reliability of a linear positional transducer (GymAware) and accelerometer (PUSH Band 2.0) for the quantification of peak punching velocity in trained junior boxing athletes. Eighteen males aged 16.7 years (±1.2) with at least two years of boxing experience participated in the study. On two separate days, participants performed five dominant-hand crosses with maximal effort. Ordinary least-products regression analysis was used to compare mean and maximum peak velocity scores between devices within each day of testing. Two-way mixed intraclass correlation coefficients (ICC3,1) and Pearson`s r with 95% confidence intervals (95%CI) were also used to compare mean and maximum peak velocity within devices across days. Maximum peak (~7.5 ms vs. ~6.2 ms) and mean peak (~7.0 ms vs. 5.4 ms) velocity was higher when measured via GymAware compared to PUSH Band 2.0 on both days (all P = 0.012). The within-device mean (ICC3,1 = 0.871, 95%CI = 0.689, 0.950) and maximum (ICC3,1 = 0.853 95%CI = 0.650, 0.942) peak velocity scores for the GymAware across Days 1 and 2 demonstrated very high reliabilities. Mean (ICC3,1 = 0.309, 95%CI = -0.170, 0.670) and maximum (ICC3,1 = 0.227, 95%CI = -0.173, 0.637) peak velocity for PUSH Band 2.0 demonstrated weak reliabilities. Proportional bias was found for Day 2 mean and maximum peak velocity and when both days were pooled. Fixed bias was observed for mean (Day 1) and maximum peak velocity when both days were pooled. These results may provide useful information for professionals working with boxing or combat-sport athletes.